Nilai-Nilai Pendidikan Antikorupsi Dalam Buku Ajar Pendidikan Agama Islam Dan Budi Pekerti Kurikulum 2013 SMA Kelas XII - Salamudin, Ceceng; Ibrahim, Ropik (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
Anti-corruption education is crucial for students to instill foundational knowledge and values that guard against engaging in corrupt practices in their future lives. Textbooks play a significant role in embedding these anti-corruption values as they contain the core educational material taught to students. This study aims to describe the anti-corruption values and their scope present in the Islamic Education and Character Development textbooks of the 2013 Curriculum for 12th Grade High School. This qualitative study uses a literature review approach based on written sources. The research employs descriptive methods and content analysis techniques to critically and constructively analyze the anti-corruption values and their scope within the Islamic Education and Character Development textbooks of the 2013 Curriculum for 12th Grade High School. The results of the study reveal four core anti-corruption values in the textbook: honesty, responsibility, fairness, and hard work. These values are specifically highlighted in Chapter 1, "Enthusiasm for Worship with Belief in the Hereafter," and Chapter 11, "Maximizing Oneself to Be the Best."  Keywords : Anti-Corruption Education Values, Islamic Education and Character Development Textbook, 2013 Curriculum, 12th Grade High School